Engineering Vibration, Communication and Information Processing ICoEVCI 2018, India - Ray, Kanad; Sharan, S. N.; Rawat, Sanyog; Jain, S. K.; Srivastava, Sumit; Bandyopadhyay, Anirban (Lecture Notes in Electrical Engineering, 2019)
This book discusses the revolution of cycles and rhythms that is expected to take place in different branches of science and engineering in the 21st century, with a focus on communication and information processing. It presents high-quality papers in vibration sciences, rhythms and oscillations, neurosciences, mathematical sciences, and communication. It includes major topics in engineering and structural mechanics, computer sciences, biophysics and biomathematics, as well as other related fields. Offering valuable insights, it also inspires researchers to work in these fields. The papers included in this book were presented at the 1st International Conference on Engineering Vibration, Communication and Information Processing (ICoEVCI-2018), India.